2020
DOI: 10.22541/au.158872422.29877395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of soil preservation for biodiversity monitoring using environmental DNA

Abstract: Environmental DNA metabarcoding is becoming a key tool for biodiversity monitoring over large geographical or taxonomic scales and for elusive taxa like soil organisms. Increasing sample sizes and interest in remote or extreme areas often require the preservation of soil samples and thus deviations from optimal standardized protocols. However, we still ignore the impact of different methods of soil sample preservation on the results of metabarcoding studies and there is no guideline for best practices so far. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The last two papers in this section provide examples of metabarcoding optimizations aiming at improving its effectiveness in biomonitoring surveys. Guerrieri et al ( 2021 ) show how soil preservation methods can affect estimates of taxonomic richness and community composition. The authors propose guidelines for optimizing soil preservation conditions in agreement with the objectives and practical constraints of the research project.…”
Section: Methodology and Comparison With Conventional Methodsmentioning
confidence: 99%
“…The last two papers in this section provide examples of metabarcoding optimizations aiming at improving its effectiveness in biomonitoring surveys. Guerrieri et al ( 2021 ) show how soil preservation methods can affect estimates of taxonomic richness and community composition. The authors propose guidelines for optimizing soil preservation conditions in agreement with the objectives and practical constraints of the research project.…”
Section: Methodology and Comparison With Conventional Methodsmentioning
confidence: 99%
“…Empirical studies have shown how sample size (Wiesel et al, 2014), extraction method (Griffiths et al, 2018), and the primers used (Schenk et al, 2019) influence diversity estimates in isolated nematode communities, but less is known about how these procedures affect the diversity estimates of other groups of soil fauna (Marquina et al, 2019). One exception is the effect of DNA extraction and storage on diversity assessments, which has received considerable attention (Delmont et al, 2011; Guerrieri et al, 2020; İnceoǧlu et al, 2010; Zinger et al, 2016). Benchmarking is a formidable challenge, but it is necessary for soil eukaryotic biodiversity assessments.…”
Section: Future Directions: Benchmarking and Standardizingmentioning
confidence: 99%
“…A total of 6.3, 7.9 and 25.7 million reads were obtained from the Bact02, Fung02 and Euka02 libraries, respectively. After read assembly, quality filtering, spurious sequence and contaminant removal, 481,411, 2,511,721 and 13,232,441 good-quality sequences remained, consisted of 660 (Bact02), 1,075 (Fung02) and 3,611 (Euka02) unique sequences (i.e., MOTUs) (Guerrieri et al, 2020).…”
Section: Re Sultsmentioning
confidence: 99%